Anti-inflammatory and anti-gouty-arthritic effect of free Ginsenoside Rb1 and nano Ginsenoside Rb1 against MSU induced gouty arthritis in experimental animals. (1st December 2020) - Liu, Yuan; Zhu, Haiyang; Zhou, Wei; Ye, Qing
Abstract: Ginsenoside Rb1 (GsRb1) is the best constituent of ginseng and although it shows clinical efficacy as an antineoplastic, antioxidative and antirheumatic agent, its oral bioavailability is poor due to its limited solubility. In this study, the solubility of GsRb1 was improved by encapsulating it in polymeric nanocapsules (encapsulation efficiency: 99.79%), therefore, improving the oral bioavailability. The encapsulation resulted in stable, homogenous and well-dispersed nano-GsRb1, whose mean particle size and zeta potential were 183.9 nm and +36.9 mV, respectively. A significant improvement was observed in the in vitro release profile of nano-GsRb1 as compared to its free form. Our study also indicated a significant repression of the degradation of nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha (IκBα), the nuclear factor kappa B (NF-κB) signaling pathway, NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome activation, and the mitochondrial damage, thereby, reducing inflammation and gouty arthritis induced by monosodium urate (MSU), when compared to free GsRb1, strongly suggesting that polymeric nano-particles can be a novel approach for delivering the GsRb1 into the inflamed joints for a better treatment effectiveness. Highlights: GsRb1 is the best constituent of ginseng. GsRb1 oral bioavailability is poor due to its limited solubility. The solubility of GsRb1 was improved by encapsulating it in polymeric nanoparticles. Nano-GsRb1 is a novel approach to deliver GsRb1.